Genealogia e clínica - Oliveira, Yan Menezes (2018)
The aim of the present work is to produce a space of intercession between the thought of the German philosopher Friedrich Nietzsche and the clinical activity, especially regarding the preoccupation of this activity with the psychic suffering. Such an approach and exchange is justified both by the philosopher's unique interpretation of suffering and sickness throughout his work, and by his approach to clinical activity when Nietzsche seeks in his work to diagnose and transform various aspects considered decadent and diseased in modernity. For the production of this space of intercession, two movements were made from the critical thinking of Nietzsche. First, a genealogical critique of the emergence of the values of the clinical model from modernity, starting from its composition during the transition from the eighteenth to the nineteenth century within Europe from medical practice, through the psychiatric clinic and reaching the psychoanalytic work of Sigmund Freud. Within this genealogical analysis, we sought to identify expressions of the "will of truth" within the theory and practice of such a clinical model, in order to counteract with Nietzsche's thinking. Secondly, the work proposed to investigate within Nietzsche's work a set of concepts that corroborated with the production of a clinical model within the psychology distant of moral prejudices that would have oriented this knowledge until Nietzsche and of the "will of truth". For that, we used the study of concepts within the author's work such as body, great reason, health, transvaluation of all values, tragic perspective and etc .. Finally, it is concluded that it is possible to approximate and create a space of intercession between Nietzsche's thought and clinical activity in order to propose a critical psychology in relation to the moral prejudices that support the will of truth about suffering.